HUMAN DEVELOPMENT IN EMERGING ECONOMIES: THE ROLE OF POVERTY, ECONOMIC GROWTH, AND LOCAL REVENUE IN JAWA TENGAH PROVINCE - Putra, Allen Pranata; Firdaus, Cecep Bryan; Syarofi, Muhammad (Jurnal Al-Ijtimaiyyah, 2025)
Human development remains a crucial challenge in developing regions, particularly in Jawa Tengah Province, which continues to face high poverty rates, fiscal disparities, and uneven access to basic services. These issues contribute to low Human Development Index (HDI) scores and hinder inclusive growth. This study aims to examine the effect of poverty rate, economic growth, and Original Local Government Revenue (OLGR) on HDI across 35 districts and cities in Jawa Tengah Province from 2019 to 2023. Employing a quantitative approach, the research applies Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS software. The findings indicate that poverty rate and OLGR have a significant effect on HDI, while economic growth does not show a statistically significant relationship. Collectively, the three variables explain 49.1% of the variation in HDI. These results highlight the importance of strengthening local fiscal capacity and implementing equitable redistribution policies to improve human development outcomes at the regional level.